The case of the Goblin Pearls. - Yep, Laurence (New York : HarperTrophy, 1997)
Lily and her aunt a Chinese American movie actress, join forces to solve the theft of some priceless pearls and stop the operator of a sweatshop in San Francisco & China town
Keywords: Mystrey and detective stories; Chinese American -- Fiction; Chinatown (San Francisco, Calif.) -- Fiction.) -- I. Title -- II. Series : Yep, Lawrence . China